DOTATATE PET Imaging in Olfactory Neuroblastoma and Association with SSTR Expression - Palmieri, Daniel E.; Tadokoro, Kent S.; Valappil, Benita; Pakala, Theja; Muthukrishnan, Ashok; Seethala, Raja R.; Snyderman, Carl H. (Journal of Neurological Surgery Part B: Skull Base, 2023)
Introduction Olfactory neuroblastoma (ONB), or esthesioneuroblastoma, is a rare neuroectodermal tumor of the nasal cavity and paranasal sinuses. Most of these tumors express somatostatin receptors (SSTRs), providing a potential target for radionuclide imaging with Ga-68 DOTATATE. However, this imaging modality has not been extensively studied in ONB.Methods We conducted a retrospective chart review of 96 endoscopic endonasal skull base surgery cases for ONB performed at our institution between 2000 and 2021. Histo (H) scores were assigned to each tumor and normalized DOTATATE standardized uptake values (nSUVs) were measured as well.Results Nine patients (5 males and 4 females) with ONB were ultimately included in the study. The average age of the patients was 50 years. All ONBs had a positive SSTR2 expression (H-score > 105; mean: 180). All ONBs showed DOTATATE avidity (mean nSUV for ONB: 6.7). However, there was no correlation between H-score and nSUV, with an r2 of 0.24 (p = 0.18).Conclusion Our study shows that SSTR2 expression is found in all ONBs with associated DOTATATE avidity, which may serve as a valuable imaging modality to monitor for recurrent and metastatic disease in ONB.
Keywords: olfactory neuroblastoma; esthesioneuroblastoma; DOTATATE; SSTR2; PET Imaging